Efficacy of Azotobactor and plant growth-regulators on productivity of wheat (Triticum aestivum) in relation to fertilizer application - Tomar, R K S; Namdev, K N; Raghu, J S; Tiwari, K P (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during the winter season of 1991-92 and 1992-93 to evaluate the efficacy of Azotobactor and plant growth-regulators on the yield of wheat (Triticum aestivum L. emend. Fiori & Paol.) in relation to N, P and K application. Yield and yield attributes of ’HI 1077’ wheat increased significantly with application of N, P and K @ 120, 26.20 and 33.33 kg/ha respectively. Azotobactor resulted in maximum dry matter/plant (16.02 g) and 1 000-seed weight (48 g), whereas cytokinin (@250 mI/ha at 30 and 45 days after sowing) gave the maximum grain weight/plant (8 g), harvest index (41.17%) and grain yield (3.053 tonnes/ha). The highest straw (4.626 tonnes/ha) was recorded with Azotobactor. Application of N, P and K @ l20, 26.20 and 33.33 kg/ha respectively + Azotobactor gave the highest grain yield (4.261 tonnes/ha).